Equimatchable claw-free graphs - Akbari, Saieed; Alizadeh, Hadi; Ekim, Tinaz; Gözüpek, Didem; Shalom, Mordechai (Elsevier, 2018)
A graph is equimatchable if all of its maximal matchings have the same size. A graph is claw-free if it does not have a claw as an induced subgraph. In this paper, we provide the first characterization of claw-free equimatchable graphs by identifying the equimatchable claw-free graph families. This characterization implies an efficient recognition algorithm. (C)2018 Elsevier B.V. All rights reserved.
Keywords: Equimatchable graph; Factor-critical; Connectivity